Application of Synthetic Filters from Polypropylene in Diesel Locomotive Oil Systems to Improve the Efficiency of Cleaning Engine Oil - Babanin, Oleksandr; Butskiy, Oleksandr; Kovalenko, Oleksandr; Maksimov, Maksym (International Journal of Engineering and Technology, 2018)
The questions of application of synthetic materials as filtering, in oil systems of internal combustion engines are considered in the article. In existing oil systems, diesel engines of internal combustion use filtering elements that provide limited protection of oil systems from particles of potentially dangerous dimensions and, therefore, wear. They are not designed to work for a long service life with the higher level of oil purity required at the present time. The urgency of these issues is caused by the need to improve the quality of engine oil cleaning and, as a consequence, to increase the reliability of the engine. The use of filter elements made of porous, fibrous polypropylene is proposed. Which, according to the results of the experiment, will allow to extend the service life of the filter elements and improve the quality of their operation.Â